La gestion communautaire des déchets : une innovation sociale à Tizi Ouzou (Algérie). Vers un modèle local de gestion ? - Ibrahim Hessas; Tarik Ghodbani (VertigO)
The objective of this article is to show how communitarian management stimulates the development of a waste management model in Tizi Ouzou (in the north of Algeria). Our hypothesis is that the application of the communitarian management for waste is a social innovation that conditions local rudological action. Semi-directive interviews with local waste stakeholders show that this practice, which began in the villages, is spreading and having a lasting impact on the public waste management system and on recovery and recycling; it brings out a multi-actor management model, based on the clarification of responsibilities and intervention scales. This model brings together various forms of waste management, differentiated resource implementations for waste, whose elaboration guided by difficulties to extend dumping disposal, teaches us to anticipate the integration of spontaneous popular practices in searching solutions for the waste problem.